2011
DOI: 10.1186/1471-2458-11-569
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency during pregnancy of HIV infected and non-infected women in tropical settings of Northwest Ethiopia

Abstract: BackgroundVitamin A deficiency (VAD) is known to be a major public health problem among women of reproductive age in South East Asia and Africa. In Ethiopia, there are no studies conducted on serum vitamin A status of HIV-infected pregnant women. Therefore, the present study was aimed at determining the level of serum vitamin A and VAD among pregnant women with and without HIV infection in tropical settings of Northwest Ethiopia.MethodsIn this cross-sectional study, blood samples were collected from 423 pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, the full extent of the problem in pregnant women is not clearly known as most of the studies were carried on preschool children. Although, WHO estimated 13.2% prevalence of VAD in pregnant women in Ethiopia (WHO, 2009), the available three studies (Wondmikun, 2005;Gibson et al, 2008;Mulu et al, 2011) conducted in the southern and north-western part of the country reported higher prevalence figures ranging from 17 to 27%.…”
Section: Introductionmentioning
confidence: 99%
“…However, the full extent of the problem in pregnant women is not clearly known as most of the studies were carried on preschool children. Although, WHO estimated 13.2% prevalence of VAD in pregnant women in Ethiopia (WHO, 2009), the available three studies (Wondmikun, 2005;Gibson et al, 2008;Mulu et al, 2011) conducted in the southern and north-western part of the country reported higher prevalence figures ranging from 17 to 27%.…”
Section: Introductionmentioning
confidence: 99%
“…This deficiency was higher than 28% in Northwest Ethiopia,[ 20 ] 31% in Nepal,[ 15 ] 2% in China, and 11.6% in Europe. [ 16 ] Maternal Vitamin A deficiency was also correlated to a reduced intra-uterine growth rate and low birth weight, and higher infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, studies conducted in sub-Saharan Africa in the 1990s provided evidence that VAD is more prevalent among HIV and tuberculosis (TB) patients and HIV + mothers. [22][23][24][25][26][27][28][29][30][31][32][33] Furthermore, serum retinol is shown to be affected by several other factors, including retinol-binding protein (RBP) synthesis in the liver; nutritional status; the levels of other nutrients, such as zinc and iron; and body mass index (BMI). [34][35][36] Studies have also shown that an increase in parity and prolonged lactation increased the risk of VAD.…”
Section: Introductionmentioning
confidence: 99%